THE EFFECTIVENESS OF ELSA SPEAK APPLICATION INTEGRATED WITH DEMONSTRATION METHOD ON STUDENTS' PRONUNCIATION PRACTICE - Aisyah Risti Wardani; Wiki Tedi Rahmawati; Syafrina Prihartini (Pedagogi: Jurnal Ilmiah Pendidikan, 2026)
This study aimed to determine the effectiveness of using the ELSA Speak Application integrated with the demonstration method on students' pronunciation practice. Pronunciation is an essential aspect of English language teaching that directly influences speaking ability, yet many students face challenges due to native language interference and lack of oral exposure. This research was conducted at SMP Plus Nusantara Medan involving 12 seventh-grade students selected through a purposive sampling technique. The research employed a quasi-experimental design with a single group pre-test and post-test design. Data were collected from the results of students' pre-test and post-test scores, which were then analyzed using statistical tests. Before hypothesis testing, normality and homogeneity tests were conducted, showing that the data were normally distributed and homogeneous. The result of the paired t-test showed a p-value (sig. 2-tailed) of 0.000, which is significantly smaller than the significance level (α=0.050). It was obtained that the t-statistical value was higher than the table t-value (43.203 > 2.201). Therefore, the null hypothesis (H0 ) was rejected and the alternative hypothesis (Ha ) was accepted. The findings demonstrate that the ELSA Speak Application integrated with the demonstration method significantly improved students' pronunciation practice. This approach is recommended as an effective teaching strategy to enhance students' phonetic skills.